Trichiasis as a clinical manifestation of subconjunctival epithelioid hemangioendothelioma: a rare case report - Hu, Mingjue; Wang, Jinlin; Zhou, Sirui; Chen, Yuanyuan; Luo, Ting; Guo, Juan; Wang, Zhanfeng; Sun, Yi (Frontiers in Oncology, 2025)
Epithelioid hemangioendothelioma(EHE) is a rare, low-grade malignant tumor of vascular endothelial origin, commonly found in the lungs, liver, bones, and soft tissue. However, orbital involvement is uncommon. This study presents a rare case of EHE located in the orbit and confined to the subconjunctival space which has not been previously documented. An elderly male patient presented with a six-month history of discomfort in his left eye, initially diagnosed with lower eyelid trichiasis and scheduled for surgical intervention. A detailed examination identified a purplish, spherical mass beneath the fornix conjunctiva of the left lower eyelid. Computed tomography (CT) imaging of the orbit revealed a well-defined soft tissue mass beneath the left globe, adjacent to the inferior rectus muscle, with no evidence of invasion into the orbital cavity. Ultrasound showed a hypoechoic mass with abundant internal vascularity. Following complete surgical excision, histopathological analysis confirmed the diagnosis of EHE. Postoperative follow-up revealed no signs of recurrence, with full resolution of the trichiasis. No eye movement disorders or visual abnormalities were observed. Despite its generally low malignancy, EHE carries a risk of recurrence and metastasis. Complete excision is crucial to minimize recurrence risk, and long-term follow-up is essential for optimal management.